A biomechanical comparison between racewalking and normal walking stance phase - Preatoni, E.; La Torre, A.; Rodano, R. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
The purpose of this study was to understand the peculiarities of lower limbs kinematics and kinetics during racewalking stance, by comparing it with normal walking gait. Four young but skilled athletes were analysed through a motion analysis system and a force platform. Results were expressed in terms of average kinetics and kinematics curves. Many differences emerged between the two walking modes, most of which can be reconducted to the rules that govern this sport. These observations might be useful, both for trainers and practitioners, to gain more insight in racewalking technique and proficiency, but they are just a first step toward an effective application ôon the fieldö. In fact, an individual analysis might discover the athletes distinctive biomechanical characteristics and consequently might help in setting better training methodologies.